This is a quadratic equation, so move all terms to one side. It's best if you keep the squared term positive.
0 = 3x^2 - 9 Divide every term by 3 to get rid of the common factor.
0 = x^2 - 3
3 = x^2
x = +/- square root of 3
2006-10-22 08:48:20
·
answer #1
·
answered by PatsyBee 4
·
0⤊
0⤋
Ok, I'm in Algebra class, so here it is:
-x^2+4=2x^2-5
-1x^2+4-(2x^2)=-5
(-1x^2)-(2x^2)+4-4=-5-4
(-1x^2)-(2x^2)=-9
-3x^4=9
Using 4 as the exponent, -3x X -3x X -3x X -3x ("x" is variable, "X" is times. Be careful.)
This = Positive 81x
81X=9
81x divides itself:81/81.
Using the Distributive property, divide both sides by 81.
81x= 9
/81 = /81
Final answer: 9/81= Simplified: 1/9!
2006-10-24 19:16:43
·
answer #2
·
answered by X 4
·
0⤊
0⤋
So its -x^2+4=2x^2-5...
ok
now add 5 to both sides.
-x^2+9 = 2x^2
now subtract -x^2. so you add it to 2x^2
9 = 3x^2
divide 9 by 3
3 = x^2
since you want x not x^2
you put a square root symbol on 3
so square root of 3 = x
(Put the square root symbol on 3, i cannot show u that because it not one of the keys on the keyboard. )lol
2006-10-22 15:55:22
·
answer #3
·
answered by CoolRunner3000 2
·
0⤊
0⤋
-x^2+4=2x^2-5
move all the x to one side and all the numbers to the other:
-3x^2=-9
x^2=3
so x= positive or negative square root of 3
Both answers work.
2006-10-22 15:51:13
·
answer #4
·
answered by D 3
·
0⤊
0⤋
1) add x^2 to both sides
2) that makes 3x^2 -5 = 4
3) Add 5 to both sides
4) That makes 3x^2 = 9
5) divide by 3
6) That makes x^2=3
7) then take square root of both sides
8) that makes x = 3^(1/2), or (-3)^(1/2)
2006-10-22 15:49:54
·
answer #5
·
answered by McNabb 3
·
0⤊
0⤋
move the -x^2 over (when you move it to the other side of the = then it changes sign so it becomes positive)
4=2x^2+x^2 -5
move the 5 over
9=3x^2
divide by 3
3=x^2
square root of 3= x
2006-10-22 15:48:09
·
answer #6
·
answered by acdshottie 2
·
0⤊
1⤋
Move -x^2:
4 = 3x^2 - 5
Move -5:
9 = 3x^2
Divide by 3:
3 = x^2
Squareroot both sides:
sqrt(3) = x
1.7 = x
2006-10-22 16:00:40
·
answer #7
·
answered by dws7011 2
·
0⤊
0⤋
subtract 2x^2 from both sides to get -3x^2+4=-5
subtract 4 from both sides to get -3x^2=-9
divide both sides by -3 to get x^2=3
take the square root of both sides to get x=+/-square root of 3
check your answer by pluggin in both answers:
-(sq.rt.3)^2+4=2(sq.rt.3)^2-5
-3+4=2*3-5
1=1
-(-sq.rt.3)^2+4=2(-sq.rt.3)^2-5
-3+4=2*3-5
1=1
both answers are correct so x=+/-sq. rt. 3
2006-10-22 15:59:46
·
answer #8
·
answered by cheesy 2
·
0⤊
0⤋
I can't show work because I don't know if I even finished the problem but I ended up with x^2=-3
2006-10-22 15:49:20
·
answer #9
·
answered by cjh4n32n 2
·
0⤊
1⤋
-x^2 +4=2x^2-5
-x^2-2x^2=-5-4
-3x^2=-9
x^2=3
x=3^(1/2)
2006-10-23 12:42:31
·
answer #10
·
answered by arpalu69 1
·
0⤊
0⤋